Multicellular Tumor Spheroids in Nanomedicine Research: A Perspective - Rossi, Martina; Blasi, Paolo (Frontiers in Medical Technology, 2022)
Multicellular tumor spheroids are largely exploited in cancer research since they are more predictive than bi-dimensional cell cultures. Nanomedicine would benefit from the integration of this three-dimensional in vitro model in screening protocols. In this brief work, we discuss some of the issues that cancer nanomedicine will need to consider in the switch from bi-dimensional to three-dimensional multicellular tumor spheroid models.